4-alkyl-L-(Dehydro)proline biosynthesis in actinobacteria involves N-terminal nucleophile-hydrolase activity of γ-glutamyltranspeptidase homolog for C-C bond cleavage - Guannan Zhong (Nature Portfolio, 2017)
γ-Glutamyltranspeptidases in gram-positive bacteria are not involved in glutathione metabolism, as their counterparts in eukaryotes and gram-negative bacteria. Here, the authors show that in Actinobacteria they catalyse the unusual cleavage of a C–C bond for the biosynthesis of non-proteinogenic amino acids.